Effect of annealing temperature on electronic structure and luminescence properties of Zn:SnO2 thin films - Varshney, Mayora; Sharma, Aditya; Parkash, Jai; Lee, B. H.; Chae, K. H.; Won, S. O. (Elsevier BV, 2025)
Connections among the metal-oxygen octahedra distortions, electronic structure perturbation and origin of photoluminescence (PL) in aliovalent element (Zn2+) doped SnO2 thin films have been investigated using the near edge X-ray absorption fine structure (NEXAFS) spectroscopy, PL spectroscopy, UV-visible absorption spectroscopy, and X-ray diffraction (XRD). The crystallite increases and the bandgap energy decreases with increasing the annealing temperature. Sn M5,4 edge and Zn L3,2-edge NEXAFS spectra have confirmed the Sn4+ and Zn2+ ions in thin films. O K-edge NEXAFS spectra convey Sn-O6 distortion. Mechanistically, different oxygen vacancies (VO0, V+1